Recovering bodies - Couser, G. Thomas (Univ. of Wisconsin Press, 1997)
A compelling look at personal narratives of HIV/AIDS, breast cancer paralysis, and deafness.
Keywords: Biografie; Acquired Immunodeficiency Syndrome; Autobiography; Biography as a literary form; Breast Neoplasms; Disabled Persons; Hearing Impaired Persons; People with disabilities; Sick; Behinderung; Krankheit; Autobiografie